The letters of Barsanuphius and John desert wisdom for everyday life - Chryssavgis, John 1958- (T&T Clark, 2022)
"Revealing unexpected truths about early desert spirituality, this volume argues that the lives of Barsanuphius and John relate closely to contemporary urban communities and how clergy tackle social challenges. The early Desert Fathers and Mothers have exercised a particular charm and appeal in recent years, but they have often been portrayed as inaccessible and eccentric figures in the history of monastic spirituality. John Chryssavgis argues that the elders have an unusual capacity to reach into the depths of the heart to reveal the extraordinary in the very ordinary, and that the correspondence between Barsanuphius and John offers an unparalleled glimpse into the sixth-century religious, political, and secular world. It opens with an exploration into the historical context of Palestinian monasticism, followed by an evaluation of the fundamental principles and practices of Barsanuphius and John"
Angekündigt mit dem abweichenden Titelzusatz "Pursuing the extraordinary in the very ordinary"
Keywords: Barsanuphius -- Sanctus -- -540; Johannes -- von Gaza -- ca. 6. Jh.; Aszetik; Spiritualität; Barsanuphius / Saint / active 6th century / Correspondence; John / the Prophet, Saint / Correspondence; Spiritual life / Orthodox Eastern Church; Asceticism / Orthodox Eastern Church; Monastic and religious life